Evaluation of the neutralizing capacity of Androctonus crassicauda (Olivier, 1807) antivenom against Leiurus quinquestriatus (Ehrenberg, 1928) venom (Scorpiones: Buthidae) - Ozkan,O (2008)
The two most venomous species of the family Buthidae, Leiurus quinquestriatus and Androctonus crassicauda, are found in Africa and in the Middle East. Potency and paraspecific activities of A. crassicauda antivenom (RSHC anti-Ac) were tested against L. quinquestriatus venom. The sera produced by Refik Saydam Hygiene Center (RSHC) showed strong reactivity against the venoms of A. crassicauda and L. quinquestriatus in western blotting and dot-blot analysis. RSHC anti-Ac presents immunoactivity and neutralizing potential against Leiurus quinquestriatus venom. Neutralization capacity of antivenom was found to be 400 µL against 40 minimum lethal doses (MLD) of A. crassicauda scorpion venom and 10 MLD of L. quinquestriatus venom. This study indicates that the RSHC anti-Ac could be used for treating L. quinquestriatus stings.